MAKAM ORANG BADUY - Boedi, Oerip Bramantyo (Kemendikbud, 2018)
Baduy people settled in Kanekes village, Leuwidamar, Lebak Regency, Banten. They still hold a long-lasting custom and religion. One of the traditions that is still ongoing is the tradition of the decay for its citizens who passed away. The Rift and the link of the tomb with the life view of Baduy people is a discussion in this study. Based on the results of observations in seven Kampung Panamping and two Kampung Tangtu seen similarities and differences in the pattern of settlements and its elements found in the grave complex. In addition, the tomb and orientation of the Baduy people also indicate the presence of symbols related to the religion of the Baduy people.